Bio-production of Ethanol in Packed Bio reactor - K Mohammed, Alaa; A. Al -Rassul, Safa; Bahjet, Mohammed (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
A lab-scale packed Bio film reactor was used for ethanol production by fermentation of sugar solution using a localisolated yeast saccharomyces cerevisia and glutaraldelryde on gelating as a covalent bounding agent. In this study fourtypes of packing in the reactor were used. They are; polypropylene mesh, glass rashig rings, ceramic rashig rings andglass beads. Glucose solutions were used as substrate with four concentrations; (5, I 0, I 5, 20 g/l). Results show that theethanol productivity was increase with increasing sugar concentration. Also it was found that polypropylene meshpacking give the highest productivity while glass beads gives the lowest productivity. The experiments were conducted atthree temperatures; 30, 35, 40'C. Highest value of productivity was obtained at 35 C. Finally results show that ethqnolproductivity increased with increasing the feed ratio of yeast / sugar.